PELATIHAN RESUSITASI JANTUNG PARU-KOMPRESI SAJA PADA SISWA SEKOLAH MENENGAH KEJURUAN KESEHATAN SEBAGAI UPAYA PENINGKATAN BYSTANDER DI MASYARAKAT - Fitri, Eka Yulia; Andhini, Dhona; Wahyuni, Dian (P3M Universitas Aisyiyah Surakarta, 2024)
The incidence of cardiac arrest often occurs in the community but in general, the public does not know what to do if they find a victim of cardiac arrest. Mortality rate due to out of hospital cardiac arrest is still very high, caused by delays in treatment of the victims. The first action to help victim is the cardioplumonary resuscitation. Cardiopulmonary resuscitation training can improve bystander knowledge and skills in performing resuscitation. The aim of this community activity programs at the Athalla Putra Palembang Health Vocational High School is provide training for students in hands only cardiopulmonary resuscitation. The methods used in this activity is lectures and simulations regarding hands only cardiopulmonary resuscitation. The results show that the average pretest score regarding knowledge about cardiopulmonary resuscitation was 5.97 and increased during the posttest with an average score of 7.87. Most participants got a score of 7 at the pretest (24,5%) while at the posttest the most participants got a score of 9 (38,8%). These results show that there is an average difference between the knowledge score before and after education regarding hands only cardioplumonary resuscitation. The participants' skills in the performing cardiopulmonary resuscitation after being given training showed that the majority of participants (55,1%) were able to demonstrate cardiopulmonary resuscitation well. Providing education on cardioplumonary resuscitation to the public should be focused on hands only CPR to make it easier for the public to provide life support to cardiac arrest victims. Keywords: community; hands only CPR; knowledge; skill; student